基于优化方法的简谐梯形通用凸轮曲线的反求设计 - 王波波; 曹巨江; 焦楠 (Jixie chuandong)
In accordance with the actual situation of engineering and customer requirements,according to the universal form of general harmonic trapezoidal motion law of cam mechanism,an inverse optimal design method of a general cam curve is proposed by use of optimization methods and MATLAB software,the cam curve that can meet the requirements better is designed.